2014
DOI: 10.1186/1472-6920-14-194
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to, and enablers of, participation in the Allied Health Rural and Remote Training and Support (AHRRTS) program for rural and remote allied health workers: a qualitative descriptive study

Abstract: BackgroundAllied health professionals play a critical role in enhancing health outcomes in primary and tertiary settings. Issues affecting the recruitment and retention of allied health workers in rural and remote areas are multifactorial. Access to relevant and effective continuing professional development is argued to be a recruitment and retention strategy for health professionals in non-metropolitan areas, however trial of the effectiveness of professional development programs and identification of enabler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…The strongest single predictor of satisfaction was program yearDennis et al 2010 [32] USALongitudinal cohortSelf-reported pre-and post-Likert scale and end-of-year reflections132 AHPsEvaluate learning from VC structured discussionsRuralNeeds based journal club - critical appraisalCritical appraisal skills; access to research and implementationAccess to research pre-to post 2006 to 2009 change of 3.10 to 3.88; critical appraisal skills change of 2.80 to 3.76; implementation change of 3.09 to 3.98DuBose et al 1997 [27]USACross sectional cohortExamination and satisfaction evaluation (5 point Likert scale)31 medical sonographersEvaluate education program comparing VC and FTFRural and metroSonographic anatomyKnowledge by rural versus classroom; overall; level of experience of participants & satisfactionStudents in remote sites did as well as those in classroom ( p  > 0.05), more years of experience had a small significant effect ( p  < 0.05, R 2  = 0.42); satisfaction evaluation was generally good (mean 3.7, range 4.9 to 2.7). However, significant difference in satisfaction between rural and classroom ( p  < 0.05) with rural indicating feelings of isolation from other students and instructor.Ducat et al2014 [20]AustraliaDescriptive QualitativeSemi-structured interviews42 AHPsEvaluate education program using blended delivery (TC, VC, FTF)Rural and remote8 domains in line with the Allied Health Capability frameworkEnablers and barriersBarriers: Competing time demands; clinical work takes precedence; difficulty accessing the equipment for VC participation.Enablers: Access to VC was cost effective; no need for travel; efficiencies with staff time.Evans & Sachs 2000 [28]USACross sectional cohortPre-and post-knowledge assessment with follow-up survey378 sonographersEvaluate a TC with an expert panelRural and urbanUltrasound equipment developmentsSatisfaction; relevance; knowledgeOverall satisfaction mean 4.5 (SD 0.60); relevance mean 4.55 (SD 0.61); between groups (managers and radiologic technologists) difference in satisfaction ( p  = 0.02) and relevance ( p  = 0.01); no gender differences in satisfaction p  = 0.72 or relevance p  = 0.94; satisfaction and relevance were correlated p  < 0.001; knowledge scores improved from 85% to 95%Fahey et al 2003 [38]AustraliaCross sectional cohortPost session evaluation, surveys and interviews38 AHPsEvaluate 12 session VC programRuralChild psychological developmentKnowledge; changes to practice; satisfaction with technologyQuestionnaires: 80% felt the sessions were informative and self-report practice change would occur; 86% comfortable with technology; 12% discomfort; several stated ‘nothing replaces person in the room’. 80% rated online medium as excellent or very good, 1% unsatisfactory / poor.…”
Section: Methodsmentioning
confidence: 99%
“…The strongest single predictor of satisfaction was program yearDennis et al 2010 [32] USALongitudinal cohortSelf-reported pre-and post-Likert scale and end-of-year reflections132 AHPsEvaluate learning from VC structured discussionsRuralNeeds based journal club - critical appraisalCritical appraisal skills; access to research and implementationAccess to research pre-to post 2006 to 2009 change of 3.10 to 3.88; critical appraisal skills change of 2.80 to 3.76; implementation change of 3.09 to 3.98DuBose et al 1997 [27]USACross sectional cohortExamination and satisfaction evaluation (5 point Likert scale)31 medical sonographersEvaluate education program comparing VC and FTFRural and metroSonographic anatomyKnowledge by rural versus classroom; overall; level of experience of participants & satisfactionStudents in remote sites did as well as those in classroom ( p  > 0.05), more years of experience had a small significant effect ( p  < 0.05, R 2  = 0.42); satisfaction evaluation was generally good (mean 3.7, range 4.9 to 2.7). However, significant difference in satisfaction between rural and classroom ( p  < 0.05) with rural indicating feelings of isolation from other students and instructor.Ducat et al2014 [20]AustraliaDescriptive QualitativeSemi-structured interviews42 AHPsEvaluate education program using blended delivery (TC, VC, FTF)Rural and remote8 domains in line with the Allied Health Capability frameworkEnablers and barriersBarriers: Competing time demands; clinical work takes precedence; difficulty accessing the equipment for VC participation.Enablers: Access to VC was cost effective; no need for travel; efficiencies with staff time.Evans & Sachs 2000 [28]USACross sectional cohortPre-and post-knowledge assessment with follow-up survey378 sonographersEvaluate a TC with an expert panelRural and urbanUltrasound equipment developmentsSatisfaction; relevance; knowledgeOverall satisfaction mean 4.5 (SD 0.60); relevance mean 4.55 (SD 0.61); between groups (managers and radiologic technologists) difference in satisfaction ( p  = 0.02) and relevance ( p  = 0.01); no gender differences in satisfaction p  = 0.72 or relevance p  = 0.94; satisfaction and relevance were correlated p  < 0.001; knowledge scores improved from 85% to 95%Fahey et al 2003 [38]AustraliaCross sectional cohortPost session evaluation, surveys and interviews38 AHPsEvaluate 12 session VC programRuralChild psychological developmentKnowledge; changes to practice; satisfaction with technologyQuestionnaires: 80% felt the sessions were informative and self-report practice change would occur; 86% comfortable with technology; 12% discomfort; several stated ‘nothing replaces person in the room’. 80% rated online medium as excellent or very good, 1% unsatisfactory / poor.…”
Section: Methodsmentioning
confidence: 99%
“…In Australia, these chronic rural health workforce shortages have been identified as significantly contributing to the substantial unaddressed health care needs found in rural and remote communities [1]. Of particular and growing concern are shortages of allied health professionals (AHPs), particularly given the greater reliance on collaborative, team-based care in rural places and the lead role that AHPs play in providing rehabilitation and chronic disease management services [2,3]. Shortages of AHPs are also likely to be a contributing factor in the lower hospitalisation rates for rehabilitation care among Australians living in rural areas, with 6.9 hospitalisations per 1000 population for outer regional areas and 6.2 for remote areas compared to 19 in major cities [1].…”
Section: Introductionmentioning
confidence: 99%
“…For example only 0.8% of psychologists practice in rural areas, compared to 79.5% in metropolitan areas [12]. This shortage is particularly alarming considering the pivotal role AHPs play in the provision of health care services, such as chronic disease management, rehabilitation and acute care [13]. Addressing the mal-distribution and lack of AHPs in rural areas is of critical importance to help improve health inequalities experienced by Australians living in rural and remote locations [10].…”
Section: Introductionmentioning
confidence: 99%
“…To date, much of the focus on addressing health workforce shortages in rural and remote Australia has had a focus on medical and nursing professions [13]. In South Australia, while the Rural Health Professionals Program (RHPP) and the Transition to Professional Practice Program (TPPP) provide financial and professional supports to all health professionals including allied health, the uptake of these programs are mostly associated with the nursing professions.…”
Section: Introductionmentioning
confidence: 99%